What factors influence women's empowerment in Ethiopia? A multilevel analysis of Ethiopia's demographic and health survey data - Dellie, Endalkachew; Tiruneh, Misganaw Guadie; Jejaw, Melak; Demissie, Kaleb Assegid; Getnet, Mihret; Belachew, Tadele Biresaw; Teshale, Getachew; Addis, Banchlay; Geberu, Demiss Mulatu; Yazachew, Lake; Tafere, Tesfahun Zemene; Worku, Nigusu (Frontiers in Global Women's Health, 2024)
BackgroundWomen's empowerment has been a global priority, as countries can achieve significant growth and economic development by empowering women. Understanding the individual and community-level factors that influence women's empowerment is crucial for policymakers to develop effective policies and to improve women's empowerment.MethodA community-based cross-sectional survey was conducted in 11 administrative regions of Ethiopia. The analysis included a weighted sample of 7,108 married women of reproductive age (15–49 years) from the 2,016 Ethiopian Demographic and Health Survey (EDHS). A multilevel mixed-effect binary logistic regression analysis was used to examine the individual and community-level factors associated with women's empowerment. In the final model, significant variables were identified using a p-value of <0.05 and an adjusted odds ratio (AOR) with a 95% confidence interval (CI).ResultsThe overall magnitude of women's empowerment was 23.7% (95% CI: 22.7–24.7). Only 30.9% of women reported participating in household decision-making, and 32.5% disagreed with all the reasons justifying wife-beating. At individual-level, factors positively associated with women's empowerment included secondary (AOR: 2.72 (1.77–4.23), and higher (AOR: 3.65 (1.81–7.34) education. However, belonging to the Muslim religion was negatively associated with women's empowerment (AOR: 0.63 (0.47–0.85). At the community level, wealthy communities were positively associated with women's empowerment (AOR: 1.60 (1.05–2.44). Conversely, residing in rural areas (AOR: 0.49 (0.29–0.83), and living in the Afar (AOR: 0.35 (0.17–0.70), Amhara (AOR: 0.45 (0.26–0.79), Oromia (AOR: 0.43 (0.26–0.73), South Nation Nationalities, and Peoples (SNNP) (AOR: 0.42 (0.24–0.75), and Gambella (AOR: 0.36 (0.20–0.66) regional states were negatively associated with women's empowerment.ConclusionThe overall magnitude of women's empowerment in this study was low. Factors that positively influenced empowerment included attending secondary and higher education, as well as residing in communities with higher wealth status. On the other hand, being Muslim, residing in rural areas, and living in the Afar, Amhara, Oromia, SNNPR, Gambella, and Tigray regions were negatively associated with women's empowerment. As a result, the government of Ethiopia needs to design community-based women's empowerment strategies and involve women in income-generation activities that improve their participation in household decision-making to empower them.